An accelerated and effective synthesis of zinc borate from zinc sulfate using sonochemistry - Ersan, Ali Can; Kipcak, Azmi Seyhun; Ozen, Meral Yildirim; Tugrul, Nurcan (DE GRUYTER POLAND SP Z O O, 2020)
Recently, sonochemistry has been used for the synthesis of inorganic compounds, such as zinc borates. In this study using zinc sulphate heptahydrate (ZnSO4 center dot 7H(2)O) and boric acid (H3BO3) as starting materials, a zinc borate compound in the form of Zn3B6O12 center dot 3.5H(2)O was synthesized using an ultrasonic probe. Product's characterization was carried out with using X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR) and Raman spectroscopy. Zinc borate compound's chemical bond structure was observed with Raman and FTIR. From the XRD results it was seen that Zn3B6O12 center dot 3.5H(2)O can be quickly synthesized upon heating at 80 degrees C and 85 degrees C (55 min) or 90 degrees C (45 min) in very high yield (>90%). The minimum particle size obtained was similar to 143 mu m from the SEM results. Zinc borate compound was synthesized at a lower temperature in less time than other synthesized zinc metal compound in literature.
Keywords: ultrasonic irradiation; sonochemistry; zinc borate; reaction yield; Chemistry